SOCIOTECH LEARNING ECOSYSTEM: STRENGTHENING STUDENTS' SOCIO-ECONOMIC RESILIENCE THROUGH COMMUNITY-BASED DIGITAL PLATFORM INNOVATION IN TOLITOLI - Ikbal; Nur Inayati Saiful; Jepri Utomo; Inayatul Mutmainnah (SocioEdu: Sociological Education, 2025)
The socio-economic resilience of students in 3T regions such as Tolitoli Regency still faces significant challenges, particularly in utilizing technology as a learning tool. This study aims to develop a Sociotech Learning Ecosystem, a community-based digital learning platform designed to strengthen students' learning skills, digital literacy, and socio-economic support. The method used is a combination of the Borg and Gall Research and Development (R&D) model modified with a Community-Based Participatory Research (CBPR) approach. The research subjects include junior high school/high school students, teachers, school principals, parents/guardians, and community partners in Tolitoli Regency. Data was collected through participatory observation, in-depth interviews, and Focus Group Discussions (FGDs), then analyzed thematically. The research findings indicate that despite the availability of digital devices and internet access, challenges such as unstable connections, low digital literacy, and limited community engagement remain major issues. The developed model successfully integrates technology, contextual learning content, and active community involvement, thereby creating an adaptive and inclusive learning ecosystem. In conclusion, the Sociotech Learning Ecosystem offers a holistic solution that can be replicated in other regions facing similar challenges, while also supporting the equitable distribution of national education quality.